Analisis Persepsi Konsumen Pada Produk Pisang Goreng Madu Di Coffee Shop: Studi Kasus Yoms Kopi & Gorengan Serpong - Murti, Aji Kresno; Kuswibowo , Christian; Erliani , Erliani (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2022)
This study aims to analyze consumer perceptions of honey fried banana products at Yoms Kopi & Gorengan Serpong. Perception analysis in this study was formed from the dimensions of the five senses, experience and individual knowledge. This research is a descriptive quantitative research using the Statistical Program for Social Science software. This study uses one variable (univariate). The object in this research is consumer perception. Sampling in this study used the Non Probability Sampling technique with the sampling method namely Purposive Sampling. Data analysis in this study included validity tests, reliability tests, and descriptive analysis. Based on the analysis of the data that has been obtained, the dimension of consumer perception that is most felt by customers on honey fried banana products at Yoms Kopi & Gorengan Serpong is the sensory dimension because the overall mean score obtained has the highest value compared to other consumer perception dimensions (4.41) and overall mean score on the dimensions of the five senses which means that all consumers/customers of Yoms Kopi & Gorengan Serpong strongly agree about feeling a different sensation when consuming Yoms honey fried bananas; Liked the Yoms honey fried banana product from the first time I consumed it; and Liked the taste of Yoms honey fried banana